INSTAGRAM DAN PERUBAHAN AKTIVITAS BERWISATA MASYARAKAT BANYUMAS - Dian Bestari Santi Rahayu; Itsna Hidayatul Khusna (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
The purpose of this study was to see changes in the tourism activities of the Banyumas community due to the presence of Instagram. This research is a qualitative descriptive study. The object of the research is tourists who visit natural and artificial tourism places in Banyumas Regency as well as tourist objects that use Instagram as a promotional medium. Data is collected through observation, surveys, interviews and documentation through literature. From the research, the results obtained are that the first Instagram plays a role in finding information about tourist objects and as a means of self-existence, tourist activity in tourist attractions is based on status and dignity, there is a strong impulse to upload photos on Instagram, a tourist attraction that gives rise to a trend of instagramble tourism, and the utilization of Instagram as a tourism promotion media in Banyumas.Keywords: Instagram, Tourism Activity, Banyumas